Exploring the Impact of Group Work on Students' Learning Outcomes: A Study in Eighth Grade of Junior High School - Turini Erawati, Linda, Ananda Tri Novianti, Rafie Shaleh, (Universitas Teuku Umar, 2025)
Increasing student involvement and academic accomplishment in junior high school, especially in the eighth Learning in junior high school, particularly in the eighth grade, can be challenging. The group work method, which is thought to be successful in encouraging cooperation, active engagement, and enhanced student learning outcomes, is one strategy used to solve this problem. This study aimed to analyze the implementation of group work and determine its impact on English learning outcomes for grade VIII students. The research used a qualitative approach with data collection techniques through interviews. The results showed that students responded positively to the group work method, which helped them understand the material and complete tasks through interaction and cooperation. In addition, group work increases students' learning motivation and cognitive engagement. However, the effectiveness of this method is affected by the internal dynamics of the group, such as participation, commitment and discipline of the members. The results of this study reveal differences in participation patterns between female students who tend to be more active than male students. Supporting factors for the success of group work include friendship relationships, leadership, and active communication, while the use of cellphones is a significant obstacle. In conclusion, the group work approach improves English learning results, but it should be noted that successful group management is crucial to its success. The study's findings show that female students participate differently than male students, who are generally more active. While camaraderie, leadership, and active communication are supportive characteristics for group work performance, cell phone use is a major obstacle. In summary, group work techniques improve English learning results, but their effectiveness depends heavily on good group administration.